2022
DOI: 10.1186/s13006-022-00511-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lullaby on volume, fat, total protein and albumin concentration of breast milk in premature infants’ mothers admitted to NICU: a randomized controlled trial

Abstract: Background Listening to music can reduce or manage stress, fatigue, and accompanying symptoms in mothers. Music increases oxytocin secretion which affects breast milk. This study aimed to examine the effect of lullaby on volume, fat, total protein and albumin concentration of breast milk in mothers of premature infants admitted to the NICU. Methods This clinical trial was performed on 100 primiparous mothers whose premature infants were hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Nine of 16 studies had high risk of bias for at least 1 outcome. Five studies reported at least 1 outcome with low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine of 16 studies had high risk of bias for at least 1 outcome. Five studies reported at least 1 outcome with low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Ten randomized clinical trials (RCTs) contributed to this outcome, measuring milk quantity expressed in neonatal intensive care unit (NICU) settings or drunk by a healthy infant at the breast (deuterium isotope or test weighing) . The studies used lactation-specific–guided relaxation, music, breathing exercises, and a mindfulness app . Five studies were at high risk of bias for this outcome (due to insufficient washout period in a crossover study, missing outcome data or selection of reporting).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations